Inflammatory cytokine and plasma C-reactive protein response to ketoacidosis in adults with type 1 diabetes: Egyptian multicenter study - Ghada A. Mohamed; Mohamed Z. Abd-Elrahman; Rania Bahriz; Ahmed Albehairy (SpringerOpen, 2020)
Abstract Background In adults with diabetic ketoacidosis (DKA), high plasma levels of C-reactive protein (CRP) and inflammatory cytokines such as interleukin-6 (IL-6) were reported to be sensitive markers of infection. However, elevation of both CRP and the pro-inflammatory cytokines which regulate CRP are probable without infection and may act as indicator of systemic inflammatory response (SIR). So, we wanted to determine if increased plasma CRP levels occur in young patients with severe DKA who do not have clinical evidence of infection and to relate observed changes in CRP level to the pro-inflammatory cytokine levels. Results Upon admission of 30 DKA patients with age ranging from 17 to 40 years, we found significant elevation of CRP (P = 0.001) and IL-6 (P = 0.001) in DKA patients than control group. After resolution of DKA, there was significant reduction in CRP and IL-6 compared to before DKA correction (P value = 0.054 and 0.001), respectively. There was a significant negative correlation between CRP after correction of DKA and RBCs (P = 0.042), and serum K (P = 0.021) and between CRP prior to DKA correction and PH (P = 0.025). Conclusions Patients with DKA without infection had increased levels of CRP and inflammatory cytokines. Intensive insulin therapy has a powerful anti-inflammatory effect that, at the time of DKA improvement, can normalize levels of CRP and inflammatory cytokines, and this beneficial effect is greater for IL-6 than CRP.